2009
DOI: 10.1111/j.1439-0523.2008.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of a novel gametocide amidosulfuron on rapeseed (Brassica napus)

Abstract: The efficiency of a novel gametocide amidosulfuron, 1-(4, 6-dimethoxypyrimidin-2-yl) -3-mesyl (methyl) sulfamoylurea, was evaluated on rapeseed (Brassica napus L.). Double application of 0.09-0.12 g/ha amidosulfuron at the uni-nucleate stage of longest buds and 12 days later, made 97.4-100% plants male-sterile in seventeen out of 20 cultivars tested. The shrunken anthers could not release pollen or produced only dysfunctional pollen grains that could not be stained by aceto carmine. The treatment also caused 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 6 publications
3
21
0
1
Order By: Relevance
“…As a result, seed purity reached 95.5% in the ZS09 × SH11 cross. Concerning the level of male sterility, time efficiency, dosage range, and yield parameters, the efficiency of MES as gametocide is comparable with two previously reported chemicals, tribenuron-methyl and amidosulphuron in rapeseed (Yu et al 2006(Yu et al , 2009. MES is very cheap and does not pose any environmental hazard or health risk (Kou et al 2006;Wang et al 2008).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…As a result, seed purity reached 95.5% in the ZS09 × SH11 cross. Concerning the level of male sterility, time efficiency, dosage range, and yield parameters, the efficiency of MES as gametocide is comparable with two previously reported chemicals, tribenuron-methyl and amidosulphuron in rapeseed (Yu et al 2006(Yu et al , 2009. MES is very cheap and does not pose any environmental hazard or health risk (Kou et al 2006;Wang et al 2008).…”
Section: Discussionsupporting
confidence: 52%
“…Our group previously identified that two acetolactate synthase inhibitor herbicides, tribenuron-methyl and amidosulphuron, can induce complete male sterility in rapeseed when applied twice at a dosage (Yu et al 2006(Yu et al , 2009. In this investigation, we reported that MES, also an acetolactate synthase inhibitor herbicide, induced complete male sterility in 48 out of 49 rapeseed accessions when applied at a concentration < 1%.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations